STUDI LITERATUR RIVIEW: HUBUNGAN KEJADIAN STRES DENGAN GASTRITIS - Hikmathine Osella Putri; Indah Rizky Siregar (Jurnal Kesehatan, 2023)
Stress can be experienced by anyone, both young adults and the elderly. Gastritis often occurs in adolescents, people who are stressed, who consume alcohol and non- steroidal anti-inflammatory drugs. Stress has a negative effect through neuroendocrine mechanisms on the digestive tract so that it is at risk for experiencing gastritis. .Stress can affect a person's eating patterns and rest periods. This results in hormonal changes in the body and an increase in stomach acid which causes gastritis. The aim of this study was to determine the relationship between stress and gastritis. The method was carried out using a literature review method by gathering information from written sources in the form of books, journals and articles. The results of this study are to present four articles related to the relationship between stress events and gastritis. The table shows that stress has a relationship with gastritis. Because stressful conditions that have negative conditions can trigger a recurrence of gastritis